2015
DOI: 10.1007/s10557-015-6589-2
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Action in Endothelial Cells: Different Patterns of Response Between Chemokine CX3CL1/CX3CR1 and TNF-α/TNFR1 Signaling Pathways

Abstract: PurposeTNF-α induces fractalkine (CX3CL1) and its receptor CX3CR1 in endothelial cells through NF-қB activation. NF-қB inhibitors may reduce the expression of CX3CL1, and modulation of the CX3CL1/CX3CR1 signaling was proposed as a new target for aspirin. We examined the effects of aspirin on CX3CL1 and TNF-α production, as well as CX3CR1 and TNFR1 expression.MethodsHUVECs isolated after term pregnancies (N = 28) were cultured in vitro. Lipopolysaccharide (1 μg/ml) was used as CX3CL1 inducer. HUVECs were expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…As a proinflammatory, pleiotropic, and homotrimeric soluble cytokine, TNF-α is involved in various metabolic disorders, such as diabetes mellitus [38] and rheumatoid arthritis [39], and disorders with an inflammatory background, including, but not limited to, atherosclerosis [40]. TNF-α results in the initiation of transcriptional responses via the rapid activation of NF-κB [41]. Chronic inflammation is also a cardinal feature of atherosclerotic vascular disease, in which TNF-α causes endothelial dysfunction that leads to reduced vasodilatory responses [42].…”
Section: Discussionmentioning
confidence: 99%
“…As a proinflammatory, pleiotropic, and homotrimeric soluble cytokine, TNF-α is involved in various metabolic disorders, such as diabetes mellitus [38] and rheumatoid arthritis [39], and disorders with an inflammatory background, including, but not limited to, atherosclerosis [40]. TNF-α results in the initiation of transcriptional responses via the rapid activation of NF-κB [41]. Chronic inflammation is also a cardinal feature of atherosclerotic vascular disease, in which TNF-α causes endothelial dysfunction that leads to reduced vasodilatory responses [42].…”
Section: Discussionmentioning
confidence: 99%
“…The substance can also have anti-inflammatory effects by preventing the activation of NF-κB (31), associated with the inhibited activation of NF-κB kinase β by aspirin, decreasing the binding activity of NF-κB DNA (32). Studies have reported that aspirin exerts certain effects on NF-κB, IL-6, TNF-α, ICAM-1, CX3CL1 and CX3CR1, which is consistent with the findings of the present study (33,34). …”
Section: Discussionsupporting
confidence: 94%
“…The activated NF-κB is transferred from the cytoplasm to the nucleus for transcription. It can transcribe a series of oncogenes related to cell growth and promote the production of tumors, so the activation condition of the NF-κB signaling pathway can be evaluated by NF-κB p65/50 (19,20). However, there are some shortcomings in this experiment.…”
Section: Discussionmentioning
confidence: 99%